2022
DOI: 10.1002/ael2.20093
|View full text |Cite
|
Sign up to set email alerts
|

Yield loss in rice by acute ozone pollution could be recovered

Abstract: Rising concentration of surface O3 threatens crop production and food security. To improve the evaluation and develop efficient adaptations, it is essential to study the effects of acute O3 pollution. We adopted this study by open‐top chamber (OTC) method and found that the fumigation of elevated O3 (NF40) for short (tillering and jointing, heading and ripening) and long periods during rice growth reduced the grain yield by 17, 19 and 25%, respectively, showing that both of the acute and chronic O3 pollution r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…They showed that, compared to a day with a maximum ozone concentration of <60 ppbv, an extra day with a peak ozone concentration of >120 ppbv is accountable for 1.1 ± 0.83% of yield loss in rice. The opentop chamber (OTC) study by Zhang et al (2022) reported that yield loss (YL) of rice is higher, when the crop is exposed to ozone continuously during its entire growth period than that episodically during its different growth stages. A decrease in surface ozone causes increase in rice production by 9.8% in the absence of anthropogenic emissions, as observed in a sector-by-sector examination of air pollution impacts on rice in China (Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that, compared to a day with a maximum ozone concentration of <60 ppbv, an extra day with a peak ozone concentration of >120 ppbv is accountable for 1.1 ± 0.83% of yield loss in rice. The opentop chamber (OTC) study by Zhang et al (2022) reported that yield loss (YL) of rice is higher, when the crop is exposed to ozone continuously during its entire growth period than that episodically during its different growth stages. A decrease in surface ozone causes increase in rice production by 9.8% in the absence of anthropogenic emissions, as observed in a sector-by-sector examination of air pollution impacts on rice in China (Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in China reported that the total relative yield losses (RYLs) of wheat and rice were 18.4–49.3% and 6.2–52.9% between 2014 and 2018, respectively [ [15] , [16] , [17] , [18] ]. Ground-level O 3 pollution can reduce individual grain weight and the number of rice grains by up to 5% and 20%, respectively [ [19] , [20] , [21] ] and of wheat by up to 18% and 11%, respectively [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%